Can Water Act as a Nucleophile in CO Oxidation Catalysed by Mo/Cu CO‐Dehydrogenase? Answers from Theory. Issue 8 (10th March 2022) - Rovaletti, Anna; Moro, Giorgio; Cosentino, Ugo; Ryde, Ulf; Greco, Claudio
Abstract: The aerobic CO dehydrogenase from Oligotropha carboxidovorans is an environmentally crucial bacterial enzyme for maintenance of subtoxic concentration of CO in the lower atmosphere, as it allows for the oxidation of CO to CO2 which takes place at its Mo−Cu heterobimetallic active site. Despite extensive experimental and theoretical efforts, significant uncertainties still concern the reaction mechanism for the CO oxidation. In this work, we used the hybrid quantum mechanical/molecular mechanical approach to evaluate whether a water molecule present in the active site might act as a nucleophile upon formation of the new C−O bond, a hypothesis recently suggested in the literature. Our study shows that activation of H2 O can be favoured by the presence of the Mo=O eq group. However, overall our results suggest that mechanisms other than the nucleophilic attack by Mo=O eq to the activated carbon of the CO substrate are not likely to constitute reactive channels for the oxidation of CO by the enzyme. Abstract : Can an activated water molecule form the new C−O bond during the CO oxidation reaction catalysed by the aerobic Mo/Cu CO dehydrogenase? Hybrid quantum mechanical/molecular mechanical modelling of the enzyme reveals which oxygen atom makes nucleophilic addition to CO.